2021
DOI: 10.3390/s21030718
|View full text |Cite
|
Sign up to set email alerts
|

Swelling-Based Distributed Chemical Sensing with Standard Acrylate Coated Optical Fibers

Abstract: Distributed chemical sensing is demonstrated using standard acrylate coated optical fibers. Swelling of the polymer coating induces strain in the fiber’s silica core provoking a local refractive index change which is detectable all along an optical fiber by advanced distributed sensing techniques. Thermal effects can be discriminated from strain using uncoated fiber segments, leading to more accurate strain readings. The concept has been validated by measuring strain responses of various aqueous and organic so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…After about 10 min, the acrylic coating gradually detached from the fiber; over the entire segment that was exposed to ethanol, the same effect was observed with acetone. Such effect was observed with non-stripped fibers [ 16 ], or the spliced fibers with metal sleeves. Observation of the fiber before and after the exposure under an optical microscope did not reveal any visible difference.…”
Section: Methodsmentioning
confidence: 88%
See 3 more Smart Citations
“…After about 10 min, the acrylic coating gradually detached from the fiber; over the entire segment that was exposed to ethanol, the same effect was observed with acetone. Such effect was observed with non-stripped fibers [ 16 ], or the spliced fibers with metal sleeves. Observation of the fiber before and after the exposure under an optical microscope did not reveal any visible difference.…”
Section: Methodsmentioning
confidence: 88%
“…The coatings were applied sequentially in liquid form and are cured by exposure to ultraviolet light. We demonstrated that coatings on commercially available fibers could be used for chemical sensing [ 16 ]. Here, we investigated methods with which different sensing elements can be realized on the same optical fiber which has multiple sections with different chemistries.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides coating stiffness, other physical and chemical interactions of the coating with the host media should be considered. For example, some polymer and acrylate coatings swell in contact with water, and the swelling depends on salt concentration, PH, and presence of other chemical substances (Bai & Seitz, 1994; Janting et al., 2019; Khanikar & Singh, 2021; McCurley & Seitz, 1991; Sedighi et al., 2021; Shakhsher et al., 1994).…”
Section: Discussionmentioning
confidence: 99%